Variations of gelatin percentages in HA-TCP scaffolds as the result of 6- and 12-hour sintering processes of blood cockle (Anadara granosa) shells against porosity - Desak Putu Sudarmi Ari; Firda Dean Yonatasya; Gita Saftiarini; Widyasri Prananingrum (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Porous scaffold is one type of biomaterial primarily employed as a bone substitute material which demonstrates superior osteoconductive and osteointegrative properties than solid scaffold since it can stimulate and accelerate the growth of new tissue. For the purposes of this study, porous scaffold was produced using hydroxyapatite-tricalcium phosphate (HA-TCP) powder derived from a synthesis of blood cockle (Anadara granosa) shells and gelatin. Purpose: The aim of this study was to reveal the effects of the percentage of gelatin in HA-TCP scaffolds derived from 6- and 12-hours sintering processes involving blood cockle shells on porosity. Methods: HA-TCP powder was derived from a synthesis of Anadara granosa shells using a hydrothermal method at 200oC with sintering periods of 6 and 12 hours. A XRD test was subsequently conducted to reveal the compositions of HA-TCP powder. The 24 scaffold samples (n=6) employed were manufactured using a freeze dry method before being divided into four groups, namely; Group 1 using 25% HA-TCP powder (a six-hour sintering process) combined with 20% gelatin, Group 2 using 25% HA-TCP powder (a six-hour sintering process) combined with 10% gelatin, Group 3 using 25% HA-TCP powder (a twelve-hour sintering process) combined with 20% gelatin; and Group 4 using 25% HA-TCP powder (a twelve-hour sintering process) combined with 10% gelatin. A scaffold porosity test was subsequently carried out using a liquid displacement method. A one-way ANOVA test was performed using SPSS, followed by a Post-Hoc LSD (p<0.05). Results: The statistical results for scaffold porosity were within the range of 67.21 -77.51%. The highest porosity was found in Group 3, while the lowest was in Group 4. Significant differences were also present in all groups. Conclusion: Variations in the percentage of gelatin can affect the porosity of HA-TCP scaffolds derived from 6-and 12 hours sintrering processes blood cockle shells. The smaller the percentage of gelatin, the higher the porosity.